2017
DOI: 10.1007/s00421-017-3723-9
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid hormones and commonly cited symptoms of overtraining in collegiate female endurance runners

Abstract: TH may be valuable in assessing the overall training state of ER. TH concentrations change too slowly to be a frequent marker of monitoring OTS, but are related to markers of decreased performance. Monitoring dietary intake, and fatigue may be predictive markers to assess OTS and training status of female ER.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 25 publications
0
21
0
2
Order By: Relevance
“…These studies have shown leptin to increase [8] or decrease [63], while ghrelin was not affected [63] by the overload training period, but both studies did not differentiate between athletes who developed FOR and those that did not have a performance decrement. Furthermore, a recent meta-analysis [32] identified that glutamine and the testosterone:cortisol ratio exhibited some consistent evidence of changes in response to overload training, while other research [64] suggests that changes in the thyroid hormones may be related to changes in performance in endurance runners [64]. However, while changes in these biomarkers occur in response to periods of overload training, these changes have not been shown to differentiate between overreached and non-overreached athletes.…”
Section: Hormonal Changesmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies have shown leptin to increase [8] or decrease [63], while ghrelin was not affected [63] by the overload training period, but both studies did not differentiate between athletes who developed FOR and those that did not have a performance decrement. Furthermore, a recent meta-analysis [32] identified that glutamine and the testosterone:cortisol ratio exhibited some consistent evidence of changes in response to overload training, while other research [64] suggests that changes in the thyroid hormones may be related to changes in performance in endurance runners [64]. However, while changes in these biomarkers occur in response to periods of overload training, these changes have not been shown to differentiate between overreached and non-overreached athletes.…”
Section: Hormonal Changesmentioning
confidence: 99%
“…However, whether these ratios are able to delineate between athletes that are FOR or not overreached remains to be determined. [64,92,93]. The natural variation in training load and other stressors may provide enough stress to induce a state of overreaching which could be captured through continuous monitoring.…”
Section: Preventing the Negative Consequences Of Overreachingmentioning
confidence: 99%
“…Os hormônios tireoidianos foram examinados em relação ao desempenho e à percepção de fadiga em corredoras de endurance por Nicoll et al (34). Os resultados mostraram que as concentrações dos hormônios tireoidianos sofreram alterações de forma muito lenta para serem utilizadas como marcadores preditores de OTS, todavia, estavam associadas ao declínio no desempenho.…”
Section: Imunológicos E Hematológicosunclassified
“…A literatura mostra que as escalas visuais analógicas são ferramentas úteis para facilmente monitorar o estado dos atletas em relação ao esforço e à fadiga. Nicoll et al (34) investigaram a relação da escala visual de fadiga em atletas femininas de ciclismo como indicador de OTS. A escala apresenta classificações de fadiga com psicometria padrão com valores de 1 a 10.…”
Section: Parâmetros Psicológicos E Interação Com Marcadores Fisiológicosunclassified
“…Leptin, whose secretion is also inhibited during intensive physical effort, also has a considerable influence on puberty [2123]. Special attention is also ascribed to the interactions between the HPG axis and testosterone, along with hyperandrogenism [2426] connected with it, and thyroid hormones [27].…”
Section: Introductionmentioning
confidence: 99%